Sociological views in the"Xumoyunnoma" - Shakirova Shoxida Yusupovna (Genius Journals, 2023)
This article aims to analyze the sociological perspectives embedded within the content of the "Xumoyunnoma," a fictional literary work. The study employs a qualitative research approach, focusing on the themes, character portrayals, and cultural representations within the text. Through a systematic examination of the "Xumoyunnoma," this research uncovers the social constructs and power dynamics reflected in the narrative and explores their implications for our understanding of society. The findings indicate that fictional works, like the "Xumoyunnoma," provide insights into societal beliefs, norms, and inequalities. The discussion section explores the significance of these sociological perspectives and concludes with suggestions for a more inclusive and critical representation of social phenomena in literature
Keywords: Sociological perspectives; Xumoyunnoma; Social constructs